Cover Feature: Supported Ru Metalloporphyrins for Electrocatalytic CO2 Conversion (ChemCatChem 8/2018). Issue 8 (24th April 2018) - Szkaradek, Kinga; Buzar, Krzysztof; Pidko, Evgeny A.; Szyja, Bartłomiej M.
Abstract : The Cover Feature shows a representation of the Ru‐porphyrin‐based artificial leaf, with a graphene sheet serving as a support. In their Full Paper, K. Szkaradek et al. describe the pathways of electrocatalytic CO2 hydrogenation to HCOOH, CH3 OH and CH4 . The results demonstrate the crucial role of the overpotential on the selectivity of the process. The role of the graphene support is also intriguing as it significantly decreases the energy needed to convert the more stable −CO compound to −CHO, and in turn facilitates the process. More information can be found in the Full Paper by K. Szkaradek et al. on page 1814 in Issue 8, 2018 (DOI: 10.1002/cctc.201701045 ).